Phatic Communication in Online English Class Discussions through Facebook Comments - Dian Rinawati; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2023)
Phatic communication refers to small talks that aim to form ties of personal union between people or the speakers. Especially in this digital age, phatic communication is somehow still used. This research aims to uncover the kinds and functions of phatic communication used by Indonesian students who have been doing online classes through Facebook, responding to their classmates’ material presentations, and having discussions in the comment column. This current study employs the qualitative method with the document analysis technique. The data of this recent study is the phatic communication used by students during the online course through Facebook, and the data was examined through document analysis techniques from the students’ Facebook comments activity in the form of words, phrases, clauses, and sentences related to phatic expressions. Moreover, the data was analyzed through the following steps: 1) labeling the related data; 2) classifying the data into its types and functions; 3) interpreting the data findings; and 4) drawing conclusions. The study’s main finding is the appearance of phatic expressions, for instance, greeting, thankfulness, compliment, apology, encouragement, and wishing to each other. As the typical conversation is made online through social media platforms such as Facebook, we suggest that some language or conversation styles like abbreviations, non-standard spelling, and emojis have also appeared.